Enhanced Water Flux of Aromatic Polyamide Membranes by Grafting Imidazolium‐Type Ionic Liquids Containing Silsesquioxane Frameworks - Zheng, Feng‐Tao; Su, Ke (Macromolecular chemistry and physics, 2024)
An imidazolium‐type room‐temperature ionic liquid containing silsesquioxane frameworks is successfully prepared. The polar ionic liquid products are grafted onto the surface of prepared aromatic polyamide (PA) membranes to improve water flux of PA membranes. Membranes grafted with an ionic liquid exhibit a water flux of 1.89 L m−2 h−1 bar−1), 48% higher than that of pure PA membranes while the salt rejection still remains at 96%. This improvement can be attributed to the enhanced hydrophilicity of the membrane surface, as evidenced by the reduced water contact angle. Imidazolium‐type ionic liquids containing silsesquioxane frameworks are prepared and grafted onto the surface of polyamide membranes to enhance the water flux of polyamide membranes. The results show that the water flux of membranes grafted with ionic liquid is increased by 48% compared with pure polyamide membranes while salt rejection is still high at 96%.